2000
DOI: 10.1007/pl00008137
|View full text |Cite
|
Sign up to set email alerts
|

Genetic study of glutathione accumulation during cold hardening in wheat

Abstract: The effect of cold hardening on the accumulation of glutathione (GSH) and its precursors was studied in the shoots and roots of wheat (Triticum aestivum L.) cv. Cheyenne (Ch, frost-tolerant) and cv. Chinese Spring (CS, moderately frost-sensitive), in a T. spelta L. accession (Tsp, frost-sensitive) and in chromosome substitution lines CS (Ch 5A) and CS (Tsp 5A). The fast induction of total glutathione accumulation was detected during the first 3 d of hardening in the shoots, especially in the frost-tolerant Ch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 41 publications
3
89
0
Order By: Relevance
“…Strong evidence for a relationship between tissue glutathione and chilling tolerance in maize has come from several studies by Kocsy and co-workers. In particular, these authors have shown that chilling tolerance is accompanied by increased g-ECS activity and GSH accumulation (Kocsy et al, 1996(Kocsy et al, , 2000a(Kocsy et al, , 2000b(Kocsy et al, , 2001b. Hence, we cloned maize genes encoding g-ECS and GSH-S.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong evidence for a relationship between tissue glutathione and chilling tolerance in maize has come from several studies by Kocsy and co-workers. In particular, these authors have shown that chilling tolerance is accompanied by increased g-ECS activity and GSH accumulation (Kocsy et al, 1996(Kocsy et al, , 2000a(Kocsy et al, , 2000b(Kocsy et al, , 2001b. Hence, we cloned maize genes encoding g-ECS and GSH-S.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf glutathione contents correlate with chilling resistance in maize (Kocsy et al, 1996(Kocsy et al, , 2000a(Kocsy et al, , 2000b(Kocsy et al, , 2001a(Kocsy et al, , 2001b. Furthermore, our previous data suggest that one factor in the sensitivity of maize to both shortterm and long-term chilling may be restrictions over glutathione reduction and cycling between cell types (Doulis et al, 1997;Pastori et al, 2000a).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Sun et al [23] observed that no PC was detected in Sedum alfredii in a mine population; instead, Zn and Pb treatments resulted in an increase in GSH, indicating that GSH might be involved in Zn and Pb accumulation and tolerance. Abiotic stresses have been previously shown to enhance GSH accumulation in the leaves and roots of various species [24], [25]. Under Cu or Cd stress, the level of GSH in the nonaccumulator was always higher than that in the hyperaccumulator, which correlated with the changes in MDA content.…”
Section: Glutathione and Phytochelatinsmentioning
confidence: 93%
“…Determination of thiols GR, protein and 35 S-radiolabelled compounds written in details by Kocsy et al (2000). The details of the western analysis of COR14b protein and the northern analysis of cor14b mRNA are described by Crosatti et al (1999).…”
Section: Biochemical and Molecular Analysismentioning
confidence: 99%